The role of visiting family member and companion of adult and elderly people according to nurse indications (Revista Latino-Americana de Enfermagem, 2005)
This qualitative study was based on Symbolic Interactionism and Grounded Theory and aimed to understand the interactive experience of visiting family members and companions of hospitalized adult and elderly people and to develop a theoretical model of this experience. Data were collected through observations and interviews. Two phenomena emerged from the data analysis: living the expectation of hospitalization and assuming the roles of a family visitor or companion. Understanding this experience increased our knowledge about the change that occurred, which was called "shifting between the role of visiting family member and companion in view of nurses' indications": sharing an experience of few pleasures in solidarity with hospitalized adult and elderly people.